Urinary Tract Infection Due to Paenibacillus alvei in a Chronic Kidney Disease: A Rare Case Report - Padhi, Sanghamitra; Dash, Muktikesh; Sahu, Rani; Panda, Pritilata (Journal of Laboratory Physicians, 2013)
Paenibacilli, the Gram positive, aerobic spore bearing bacilli are found normally in the environment. Though these organisms were not known to cause human disease, until recently; few species of this genus have been reported to cause infections in humans. We report here, a case of urinary tract infection in a 60-year-old chronic kidney disease patient due to this rare bacterium. The patient presented with complains of fever, dysuria, and flank pain. Routine and microscopic examination of urine revealed no abnormality except plenty of pus cells and albumin (1+). Bacterial culture showed significant bacteruria and the isolated bacteria was identified to be Paenibacillus alvei based on standard biochemical reactions.
Keywords: Chronic kidney disease; Paenibacillus alvei; urinary tract infection